ANALISIS FAKTORFAKTOR YANG MEMPENGARUHI NILAI PRODUKSI PADA PERUSAHAAN INDUSTRI FURNITURE BERSKALA BESAR DI PROPINSI JAWA TENGAH TAHUN 2004 - Maduretno Widowati (STIE Pelita Nusantara Semarang, 2007)
The purpose of this researched is to find dominant factors have an effect on to production rate at manufacturing industry of furniture big scale company with labour more than 100 people, influencing factors production rate at this research among others : labour, worker fee, fuel and lubricants cost , electricity purchased and raw materials cost.This research is manufacturing industry furniture in Jawa Tengah by exploiting data sekunder of BPS. The big factor of its influence to production rate is resouces and is costly of raw materials where raw material of furniture industry the core important is wood . This matter because of bouncing up its of marketing wood price effect of discontinuing of practice of ilegal logging andalso limitation of wood raw material in Jawa Tengah. Labour also become factor having an effect on to remember industry of furniture this of its process very is requiring of skillful hands touch (made hand). Fee worker factor, fuel and lubricants cost and electricity purchased less is having of share which is signifikan at makeup of result of production rate of furniture industry.Considering this industrial sector enough become pledge in dig of area foreign exchange , hence him presumably require to strive to answer solution of problems related to effort improve production rate in the future, either by government , private sector and also society